Der Wind in den Weiden eine Walt-Disney-Produktion nach einer Geschichte von Kenneth Grahame - Grahame, Kenneth (Walt Disney Animation Collection)
Kenneth Grahame's 1908 children's novel, "The Wind in the Willows", is a classic many times over, and Disney's animated short film remains the most memorable animated version, though wholesale changes have been made. Missing is the slow beginning with Otter and the rowing excursion, with the Disney crew jumping right into a description of the rich but highly eccentric Thadeus Toad, who lives in a mansion named Toad Hall and whose best friends are Badger, Ratty, and Mole, then getting right to his latest obsessions: horses followed by motorcars ... It's directed by Disney cartoon veteran Jack Kinney and James Algar, who supervised "The Sorcerer's Apprentice" segment on "Fantasia" (1940) and also directed many of Disney's True-Life Adventure films. Though "Wind in the Willows" is a condensed version of the 300+ page novel, it's still an effective narrative. It wouldn't surprise me, though, if a full-length remake were on the horizon. [www.moviemet.com]